Tafsir Fiqhiy: Potret Pemikiran Al-Jashshāsh dalam “Aḥkām Al-Qur’ān” - Lilik Ummi Kaltsum (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
The “Aḥkām al-Qur’ān” by al-Jashshāsh is highly regarded by scholars of Islamic jurisprudence, including subsequent commentators, both supportive and critical of it. “Aḥkām al-Qur’ān,” this is the title chosen by al-Jashshāsh for his work without the mention of the word “tafsir” like other exegesis books. Only 81 surahs are discussed, with the writing system following the order of the mushaf. The method of interpretation is predominantly bi al-ma’tsūr. Al-Jashshāsh seeks to incorporate the principles of his school of thought into the verses under discussion, expanding his interpretation beyond the main topic of the verse and appearing as a Hanafi legal book.